2019
DOI: 10.22159/ijap.2020v12i2.35896
|View full text |Cite
|
Sign up to set email alerts
|

The the Effect of Almond Oil on the Permeability of Ketoprofen Hydrogel

Abstract: Objective: The object of this study is to formulate ketoprofen hydrogels and to evaluate their permeability following the incorporation of almond oil as a penetration enhancer. Methods: Five formulas (F2-F6) of ketoprofen hydrogels were formulated with the employment of carbopol 940 and triethanolamine. A gradual increase in the amount of almond oil was used in each formula. In vitro penetration and release kinetic study was conducted for all the formulations and compared with the control formula (F1) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Fatty acids are used in the formulation of topical dosage forms as penetration enhancers, as exemplified by oleic acid (the most popular fatty acid used) [4]. In addition, they form the major component of many natural oils, such as olive oil and almond oil [29,110]. Fatty acid-containing carrier oils have been used widely in the development of transdermal dosage forms to enhance the permeation of hydrophilic and lipophilic drugs [111,112].…”
Section: Fatty Acid Containing Vegetable Carrier Oilsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fatty acids are used in the formulation of topical dosage forms as penetration enhancers, as exemplified by oleic acid (the most popular fatty acid used) [4]. In addition, they form the major component of many natural oils, such as olive oil and almond oil [29,110]. Fatty acid-containing carrier oils have been used widely in the development of transdermal dosage forms to enhance the permeation of hydrophilic and lipophilic drugs [111,112].…”
Section: Fatty Acid Containing Vegetable Carrier Oilsmentioning
confidence: 99%
“…In in vitro permeation studies, almond oil has been used to enhance the permeation of ketoprofen, clotrimazole, and pioglitazone from a gel formulation [29,41,124,125]. In vitro permeation studies have also demonstrated enhancement of timolol and ketoprofen permeation from a transdermal patch formulation containing almond oil [125,126].…”
Section: Almond Oilmentioning
confidence: 99%
See 1 more Smart Citation